Development Of Management Training System In Providing Trainee At Wedding Organizer Delapan Planner, Denpasar, Bali - Aprilia, Raisya Putri; Wahyuni, A. A. Nyoman Sri; Lumanauw, Nelsye (Politeknik Internasional Bali, 2024)
Delapan Planner is one of the recommended wedding organizers in Bali. The training management system at Delapan Planner is self-taught and conducted directly in the field. However, the trainees lack learning references, leading to less efficient work performance. The purpose of this study was to develop a training management system for the trainees at Delapan Planner to enhance their efficiency and effectiveness. This study employed a qualitative descriptive research method. Data collection techniques included observation, interviews, and documentation. Data were analyzed using a fishbone diagram to identify the root causes of the problem, focusing on four factors: methods, people, materials, and measurements. Additionally, the POAC Theory (Planning, Organizing, Actuating, Controlling) was applied. The results revealed that project improvements in the training management system were developed and systematically structured using the POAC theory. These improvements included creating training guidelines, refining training SOPs, and enhancing team communication. The study suggests that Delapan Planner updates its training management system by implementing a more structured training program. This approach is expected to improve the quality of service provided to trainees, thereby enhancing the company's overall performance more effectively and efficiently.